Origin of unipolar half-cycle pulses generation in inversion symmetric media. (16th September 2015) - Song, Xiaohong; Hao, Zhizhen; Yan, Ming; Wu, Miaoli; Yang, Weifeng
Abstract: We investigate the physical mechanism of unipolar half-cycle pulses generation in resonant two-level media with inversion symmetry. The unipolar half-cycle pulse contains substantial nonzero dc or zero-frequency component in its Fourier spectrum of the electric field. Here the origin of zero-frequency component generation in inversion symmetric media driven by symmetric electric field is identified. We show that in the regime of extreme nonlinear optics, i.e. the Rabi frequency is comparable to or even larger than the carrier frequency of the laser pulse, the time evolution of the polarization can display obvious up-down asymmetric structure under certain conditions, which manifests in the zero-frequency component generation, and is responsible for the formation of unipolar half-cycle pulses in the course of pulse propagation.